Complex-Dynamical Nanobiotechnology Paradigm and Intrinsically Creative Evolution - Kirilyuk, A.P. (Наносистеми, наноматеріали, нанотехнології, 2016)
Complex nanosystem dynamics is analysed by the unreduced solution of arbitrary many-body interaction problem, leading to the fundamental dynamic multivaluedness and universal definition of dynamic complexity in terms of the number of system realisations. As shown, the genuine quantum and classical chaos can only be strong for a free-interaction nanoscale system providing exponentially huge, ‘magic’ efficiency of such unreduced interaction dynamics, which underlies the properties of life, intelligence, and consciousness. Various more or less chaotic regimes of irreducibly complex nanosystem dynamics as well as the rigorously specified transitions between them are reviewed. The obtained unified formalism for description of the unreduced complex nanosystem dynamics is based on the universal symmetry (conservation and transformation) of complexity unifying the extended versions of all usual laws and principles. The main principles of thus obtained new, complex-dynamical nanobiotechnology paradigm are summarised, and as shown, it is the only viable way of further sustainable nanotechnology and society development in the spirit of coevolution of the natural and artificial system complexity. Складну динаміку наносистем проаналізовано за допомогою нередукованого розв'язку задачі довільної взаємодії багатьох тіл, яка приводить до фундаментальної динамічної багатозначности й універсального визначення динамічної складности у термінах кількости реалізацій системи. Показано, що в системі наномасштабних розмірів справжній квантовий і класичний хаос може бути тільки сильним, зумовлюючи експоненційно величезну, «магічну» ефективність динаміки такої нередукованої взаємодії, яка лежіть в основі властивостей життя, інтелекту та свідомости. Розглянуто різні, більш або менш хаотичні режими нередукованої складної динаміки наносистем, а також строго визначені переходи між ними. Одержано об'єднаний формалізм опису нередукованої складної динаміки наносистем, що ґрунтується на універсальній симетрії (збереженні та перетворенні) складності, яка поєднує розширені версії усіх звичайних законів і принципів. Оглянуто основні засади одержаної таким чином нової парадигми складно-динамічної нанобіотехнології та показано, що це єдиний шлях наступного сталого розвитку нанотехнології і суспільства у дусі коеволюції складности природніх і штучних систем. Сложная динамика наносистем проанализирована с помощью нередуцированного решения задачи произвольного взаимодействия многих тел, которое приводит к фундаментальной динамической многозначности и универсальному определению динамической сложности в терминах числа реализаций системы. Показано, что в системе наномасштабных размеров истинный квантовый и классический хаос может быть лишь сильным, давая экспоненциально огромную, «магическую» эффективность динамики такого нередуцированного взаимодействия, которая лежит в основе свойств жизни, интеллекта и сознания. Рассмотрены различные, более или менее хаотичные режимы нередуцированной сложной динамики наносистем, а также строго определённые переходы между ними. Полученный объединённый формализм описания нередуцированной сложной динамики наносистем основан на универсальной симметрии (сохранении и превращении) сложности, которая объединяет расширенные версии всех обычных законов и принципов. Рассмотрены основные принципы полученной таким образом новой парадигмы сложно-динамической нанобиотехнологии и показано, что это единственный путь последующего устойчивого развития нанотехнологии и общества в духе коэволюции сложности естественных и искусственных систем.